On the Discrete Orlicz Electrostatic q-Capacitary Minkowski Problem - Yibin Feng; Yanping Zhou (Journal of Function Spaces)
We establish the existence of solutions to the Orlicz electrostatic q-capacitary Minkowski problem for polytopes. This contains a new result of the discrete Lp electrostatic q-capacitary Minkowski problem for p<0and 1<q<n.